Penilaian Risiko Sanitasi Kabupaten Badung Menggunakan Pendekatan EHRA (Environmental Health Risk Assessment) - Wiraatmaja, I Putu Prana; Putri, Putu Indah Dianti (Environmental Research Center (PPLH) of Udayana University, 2024)
Proper and safe sanitation is the main foundation for public health and improving the quality of life. Although the majority of Indonesia's population has access to adequate sanitation, significant challenges are still faced in achieving safe and quality sanitation. This research aims to provide a comprehensive picture of sanitation conditions in Badung Regency, Bali Province, by focusing on key factors such as water sources, domestic wastewater, waste, standing water, and clean and healthy living behavior (PHBS). Using the Environmental Health Risk Assessment (EHRA) approach, this research involved surveys in six sub-districts with a total of 62 villages/urban village, involving 2480 female respondents aged 18-60 years as housewives. Data collected involved interviews, observations and questionnaires, with analysis carried out using EHRA tools. The research results show that Badung Regency faces five main challenges in sanitation, namely varied water sources, awareness of domestic wastewater which still needs to be improved, solid waste and waste management problems, risk of waterlogging and heterogeneous levels of PHBS in the community. The results of the Sanitation Risk Index (IRS) analysis show a number of villages/urban village with varying levels of risk, namely 18 villages/urban village with low risk, 14 villages/urban village with moderate risk, 2 villages/urban village with high risk and 28 villages/urban village with very high risk.